Synthesis of (+)-harmicine - Mondal, Pravat; N. P. Argade (Synthesis-Stuttgart, 2014)
A facile convergent access to the important indole alkaloid (+)-harmicine is described, starting from tryptamine and (R)-acetoxysuccinic anhydride via the corresponding acetoxysuccinimide in very good overall yield. Regioselective reduction of an unsymmetrical imide carbonyl group and acid-catalyzed stereoselective intramolecular cyclization were the key features involved. The directing group to induce asymmetry was finally detached via the corresponding iodide by using tributyltin hydride chemistry.
Keywords: alkaloids; cyclization; imides; reduction; stereoselective synthesis

Stereoselective synthesis of (-)-desethyleburnamonine, (-)-vindeburnol and (-)-3-epitacamonine: observation of a substrate dependent diastereoselectivity reversal of an aldol reaction - Mondal, Pravat; N. P. Argade (Organic & Biomolecular Chemistry, 2016)
Starting from (-)-acetoxyglutarimide, the enantioselective multistep synthesis of (-)-desethyleburnamonine, (-)-vindeburnol and (-)-3-epitacamonine has been demonstrated via a common hydroxyl-lactam intermediate with very good overall yields. The acetoxy function from (-)-acetoxyglutarimide was initially used as a handle to induce enantioselectivity and then as a latent source of the ketone carbonyl group. Most importantly, substrate dependent reversal of the diastereoselectivity in ester aldol reactions of hexahydroindolo[2,3-a] quinolizinones has been reported.